Mitochondrial DNA short tandem repeats unveil hidden population structuring and migration routes of an endangered marine turtle. Issue 4 (14th May 2018) - Tikochinski, Yaron; Bradshaw, Phil; Mastrogiacomo, Angela; Broderick, Annette; Daya, Alon; Demetropoulos, Andreas; Demetropoulos, Simon; Eliades, Nicolas‐George; Fuller, Wayne; Godley, Brendan; Kaska, Yakup; Levy, Yaniv; et al.
Abstract: The assessment of the composition and dynamics of endangered populations is crucial for management and conservation, and appropriate genetic markers are critical. The genetic structuring of the Mediterranean green turtle ( Chelonia mydas ) populations and the origin of the stranded animals found along the Israeli coast was investigated using new highly polymorphic short tandem repeat (STR) markers. The structuring of nesting populations was studied using pairwise genetic distances and a principal coordinates analysis (PCoA). The contribution of the different nesting populations to the stranded sample was assessed by using a mixed‐stock analysis. A clear population genetic structure, not detected before, has been revealed. The four nesting populations are genetically well differentiated, and thus should be considered as different management units. The populations from Turkey and Israel showed higher resemblance, despite residing at opposite ends of the Mediterranean distribution. The Turkish nesting population is the main source of the stranded turtles sampled along the Israeli shore, confirming that individuals from this population migrate from north to south along the eastern shore of the Mediterranean, as previously shown by telemetry studies. The use of a highly polymorphic haplotyping method enabled the detection of a clear genetic structuring of the green turtle populations in the eastern Mediterranean Sea that was not revealed in previous studies, demonstrating the importance of marker selection in population genetics. The analysis of the genetic composition of the stranded turtles allowed us to investigate the migration patterns from nesting to foraging areas, supporting previous satellite‐tracking and stable‐isotope results. These results will help to delineate conservation management units for the species in the Mediterranean, and reveal connectivity among beaches and mixed aggregations.